Extracellular-Matrix Mechanics Regulate the Ocular Physiological and Pathological Activities - Ran Zhang; Bo Li; Heng Li (Journal of Ophthalmology)
The extracellular matrix (ECM) is a noncellular structure that plays an indispensable role in a series of cell life activities. Accumulating studies have demonstrated that ECM stiffness, a type of mechanical forces, exerts a pivotal influence on regulating organogenesis, tissue homeostasis, and the occurrence and development of miscellaneous diseases. Nevertheless, the role of ECM stiffness in ophthalmology is rarely discussed. In this review, we focus on describing the important role of ECM stiffness and its composition in multiple ocular structures (including cornea, retina, optic nerve, trabecular reticulum, and vitreous) from a new perspective. The abnormal changes in ECM can trigger physiological and pathological activities of the eye, suggesting that compared with different biochemical factors, the transmission and transduction of force signals triggered by mechanical cues such as ECM stiffness are also universal in different ocular cells. We expect that targeting ECM as a therapeutic approach or designing advanced ECM-based technologies will have a broader application prospect in ophthalmology.